Everyday Life and Everyday Communication in Coronavirus Capitalism - Christian Fuchs (tripleC: Communication, Capitalism & Critique, 2020)
In 2020, the coronavirus crisis ruptured societies and their everyday life around the globe. This article is a contribution to critically theorising the changes societies have undergone in the light of the coronavirus crisis. It asks: How have everyday life and everyday communication changed in the coronavirus crisis? How does capitalism shape everyday life and everyday communication during this crisis?